Literature Study: Performance-Based Village Fund Budgeting To Achieve Good Village Governance - Wulandari, Nurlaily (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
In the era of government decentralization in Indonesia, village fund management became the main focus for increasing community development and empowerment. However, in practice, there are still various challenges that impede the implementation of good governance at the village level. In this study, a comprehensive literature review was conducted to gather information from previous research regarding the management of Village Fund Allocations (ADD) and efforts to realize good village governance. The results of the study show that the effectiveness of village fund management is influenced by factors such as planning, implementation, monitoring, reporting, and community participation. There are also findings indicating that the use of information technology, human resource competence, and organizational commitment have an effect on the accountability of village financial management. Therefore, more in-depth efforts are needed to understand and apply the principles of good governance in managing village funds in order to achieve better development and public services.